Personhood as Ongoing Gift from Others and to Others - Bracken, Joseph A. (Horizons, 2018)
Human personhood should be understood as a gift from and to others as well as a permanent and unchanging attribute of what it means to be a human being, for this understanding of human personhood fits better within a contemporary systems-oriented approach to reality. Likewise, for Christians it can also be seen as derivative from a more contemporary process-oriented understanding of the doctrine of the Trinity, namely, as co-constitutive members of a transcendent community or archetypal life-system. Finally, given the individualistic character of contemporary Western culture, an emphasis on the interdependence of entities on one another rather than on their independence from one another seems to be more needed at the present moment.